The secondary antibody response induced in tissue cultures - Sterzl, J; Milerová, J; Macková, L; Trávnícek, J (Folia microbiologica, 1993)
The conditions for induction of memory cells (B-MC) and evocation of the secondary antibody (Ab) response in tissue cultures (TC) were estimated. (1) In vivo primed B-MC cells were isolated 6-150 d after priming and stimulated in TC with different doses of sheep red blood cell (SRBC) antigen. The Ab response has a strict time and dose dependence: only small doses (10(5)) evoke a secondary response, high doses (10(8), 10(9)) a state of immediate tolerance. (2) Antigen added to TC directly with B-MC rescued their Ab production for a long period. Addition of the antigen 1 or 2 d after setting the TC, follows the Ab-response decay, comparable with virgin cells (B-ICC). (3) Primed B-MC stimulated in TC responded preferentially with an IgM secondary response; the same cell suspension adoptively transferred into isologous recipients switched into IgG cells. (4) Virgin, immunocompetent, B-ICC were primarily stimulated in TC with a small dose of antigen (10(5) SRBC); after 7 d of cultivation the cells were transferred into isologous recipients, SCID mice and into TC. In all cases, the secondary response of IgM was determined, 10 times higher than in the primary controls.
Keywords: Animals; Rabbits; imunoglobulin G; slezina; Antibody Formation; imunoglobulin M; Mice; tvorba protilátek; Mice, Inbred BALB C; kultivované buňky; myši; Immunoglobulin G; Cells, Cultured; Culture Techniques; myši inbrední BALB C; Immunoglobulin M; B-Lymphocytes; Spleen; kultivační techniky; B-lymfocyty; imunologická paměť; králíci; zvířata; Immunologic Memory